Data for "Microstructural mapping of A. islandica shells reveals environmental and physiological controls on biomineral size" - Höche, Nils; Walliser, Eric O.; Schöne, Bernd R. (Zenodo, 2021)
This data contains the image segmentation workflow, data processing procedure and all data generated for the publication "Microstructural mapping of A. islandica shells reveals environmental and physiological controls on biomineral size" currently under review. : This research was funded by a grant from the German Research Foundation (DFG) to BRS (SCHO793/20-1).